Okun’s law across time and frequencies - Aguiar-Conraria, Luís (2019)
We present the first assessment of U.S. Okun’s Law across time and frequencies, with a set of continuous wavelet tools that allows for estimating Okun’s coefficient and the lead/lag of output over unemployment at each moment of time for each cyclical frequency. We find similar results for the gaps and the first differences specifications at business cycles frequencies, but not at medium and long run cycles. Okun’s coefficient has increased (in absolute value) since the mid-1960s, except in 1985-1995, and is not particularly sensitive to recessions. The lead of output varies considerably along time and also at the different frequencies.